The impact of COVID‐19 outbreak on the Transfusion Medicine Unit of a Northern Italy Hospital and Cancer Centre. Issue 2 (22nd June 2021) - Schiroli, Davide; Merolle, Lucia; Molinari, Giuseppe; Di Bartolomeo, Erminia; Seligardi, Daniela; Canovi, Laura; Pertinhez, Thelma A.; Mancuso, Pamela; Giorgi Rossi, Paolo; Baricchi, Roberto; Marraccini, Chiara
Abstract: Background and Objectives: The first wave of coronavirus disease‐2019 (COVID‐19) dramatically affected the Transfusion Medicine Unit of the Azienda Unità Sanitari Locale ‐ Istituto di Ricovero e Cura a Carattere Scientifico (AUSL‐IRCCS) di Reggio Emilia, which faced a total rearrangement of the procedures for donors and patients. This study aims to assess the major implications of COVID‐19 on our department, focusing on the blood transfusion chain and therapies, in order to support transfusion specialists in seeking efficient ways to face similar future emergencies. Materials and Methods: This retrospective study compares our Transfusion Medicine Unit data collected between February and May 2020 with the same period in 2017–2019. Data on red blood cells and platelets donations, transfusions and clinical procedures were collected as aggregates from our internal electronic database. Results: During the lockdown, donor centres were re‐organized to reduce the risk of contagion and avoid unnecessary blood collection. Blood donations were re‐scheduled to meet the decrease in elective surgery; consequently, plateletapheresis was implemented to supply the reduction of buffycoat‐derived platelets. Transfusions significantly decreased together with orthopaedic and vascular surgery, while they were only marginally diminished for both cancer and onco‐haematological patients. Reduced procedures for inpatients and outpatients were matched by remote medicine, addressing the need of a constant healthcare support for patients with chronic diseases. Conclusions: The described measures were adopted to avoid excessive blood collection and expiration, guarantee the safety of our ward (for both patients and staff) and supply the necessary transfusion therapies. These measures may support the development of appropriate risk management plans and safety procedures for other hospitals and transfusion services that have to face similar events.